Optimising the sealing station in production process of tubes for catalytic converters involving SMED method – a case study - Dąbrowska, Magdalena; Maciejewska, Katarzyna (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2022)
The article presents the stages of the development of the lean management concept. The authors presented the SMED methodology. They made the analysis of the sealing station in the production process of tubes for catalytic converters in relation to the real model. Optimisation the sealing station in production process of tubes for catalytic converters has been done in this article. For this purpose was used one of the tools of Lean Manufacturing, SMED. Diagnosis of machine changeover operations was carried out and also measurement of the times necessary for doing these operations. Using spaghetti diagram, the path which is covered by the operator during machine changeover, was shown. Delegation of specific tasks carried out previously by the operator to production workers and implementation of organisational and technical solution has had the effect of relieving of the operator and shortening of time necessary for machine changeover and increasing productivity at the sealing station. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)